2008
DOI: 10.1111/j.1365-3156.2007.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascertainment of childhood vaccination histories in northern Malawi

Abstract: Summaryobjective To assess factors related to recorded vaccine uptake, which may confound the evaluation of vaccine impact.methods Analysis of documented vaccination histories of children under 5 years and demographic and socio-economic characteristics collected by a demographic surveillance system in Karonga District, Malawi. Associations between deviations from the standard vaccination schedule and characteristics that are likely to be associated with increased mortality were determined by multivariate logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 14 publications
4
31
1
Order By: Relevance
“…A similar pattern was reported in one study from Malawi [29] while another from China found home birth to be independently predictive of immunisation delays [28]. It is not uncommon for birth order to be associated with immunisation delays [6,7,28,34,35] but no such evidence was found in this study in line with some other studies [29]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar pattern was reported in one study from Malawi [29] while another from China found home birth to be independently predictive of immunisation delays [28]. It is not uncommon for birth order to be associated with immunisation delays [6,7,28,34,35] but no such evidence was found in this study in line with some other studies [29]. …”
Section: Discussionsupporting
confidence: 92%
“…Some of the prominent risk factors in this study are rarely reported possibly because of the younger age profile and method of recruitment for this study compared with similar studies [5,6,8,15,28,29]. For instance, the protective effect of treated neonatal hyperbilirubinaemia is unlikely to be detected or of interest in studies among older infants.…”
Section: Discussionmentioning
confidence: 80%
“…12,28 It may be because 81% of the population in Nyanza Province lives within 5 km of a public health facility, suggesting that access may be less of a barrier to vaccination uptake than in areas where health facilities may be farther away. 29 Additionally, mothers may go to multiple facilities for vaccination depending on the perceived availability of vaccinations and quality of care at the facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Malawi showed a BCG scar rate of 70% among children without documents, making it clear how vaccination coverage can be underestimated if children without vaccination cards are classified as unvaccinated. 26 We also registered pregnancies and births and could thereby determine date of birth fairly precisely if there was no written record.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%